Image processing of tree roots - Yow, Eugene Cheng Pang (Nanyang Technological University, 2020)
Being part of the quintessence of life, trees are indisputably important to mankind as they provide valuable sources needed for survival. Thus, it is extremely important to integrate trees in our daily lives and balance the ecology of trees and the human globalisation. In Singapore, where it is internationally renowned as a Green City, has over 2000 recorded native plant species and more than 2 million trees planted along the roadsides, parks, and even by the housing apartments [1]. And since so many trees are being grown in our urban jungle, it is essential to monitor the health of the trees and take note of the diseased trees to prevent deadfalls from harming the properties or even hurting the public. One method to monitor the health of the trees and determine if it is diseased is to look for signs of degradation or decomposition in the tree roots and tree trunk itself as they will reflect the status of the trees’ health and the environment and condition of the soil. If there are any signs of degradation or decomposition found in the tree roots or tree trunks, the likelihood of the tree to produce deadfall or toppling over will increase exponentially. Currently in the market, there is the ground penetrating radar, which uses the reflected electromagnetic waves to determine the location of stuffs being buried underground. The GPR uses transmitting antenna to transmit the electromagnetic wave and a receiving probe to receive the electromagnetic wave being reflected by the things buried underground.[3] Since the usage of the GPR is highly non-destructive to the environment and to the tree itself, it is one of the better approach to scan for buried items underneath the surface. Other usages of the GPR includes search for underground water cavities [5], the marking of anti-personnel mines [6] and the identification of archaeological features being buried underground [4] However, the GPR has its own limitations as they could not analyse the data and distinguish the healthy tree roots and the diseased ones. Thus, the aim of this project is to research and aid in the creation of a GPR that could also identify which tree roots are diseased and map out the span of the tree roots and this report presents the researches done to aid in a creation of a GPR that would identify and map out tree roots.